PENGARUH KEGIATAN OUTBOUND TERHADAP PERKEMBANGAN MOTORIK KASAR ANAK USIA DINI DI RA AL-FURQON MADINA - Annisa Nur; Irma Suryani Siregar; Riska Yulia; Amaliah Amaliah; Robiatul Adawiyah; Hesti Mayasari; Rosmidar Rangkuty (STKIP Pesisir Selatan, 2026)
One learning strategy that can be implemented to stimulate gross motor skills is outbound activities. Outbound activities are outdoor learning activities packaged in the form of educational games, physical challenges, and group collaboration. Outbound activities are one of the experiential learning strategies that are effective in stimulating the gross motor development of early childhood. This article aims to describe the implementation of outbound activities and their impact on the gross motor development of children at RA Al-Furqon during the Field Experience Practice (PPL) activities. The method used is qualitative descriptive with observation, documentation, and learning practice reflection techniques. The subjects of the activity are children from groups A and B at RA Al-Furqon, totaling 125 children. The results of the practice show that outbound activities such as balloon shaking, marble relay, ball relay, and balance games are able to improve motor coordination, agility, large muscle strength, as well as children's self-confidence. With careful planning and optimal supervision, outbound activities become a fun and effective learning alternative in developing the gross motor skills of early childhood.